Chemical Characteristics of Three Kinds of Japanese Soy Sauce Based on Electronic Senses and GC-MS Analyses - Zhao, Guozhong; Feng, Yixu; Hadiatullah, Hadiatullah; Zheng, Fuping; Yao, Yunping (Frontiers in Microbiology, 2021)
Japanese soy sauce has become more acceptable by Chinese consumers due to its umami taste. However, the volatile flavor compounds and taste characters have not been fully clarified. This study was aimed to explore the flavor characteristics of three kinds of Japanese soy sauce, including Koikuchi Shoyu, Usukuchi Shoyu, and Amakuchi Shoyu. The secret of volatile flavor substances was investigated by GC-MS and electronic nose, and taste compounds by silylation GC-MS and electronic tongue. A total of 173 volatile flavor substances and 160 taste compounds were identified. In addition, 28 aroma compounds with odor activity values (OAV) 1 were considered as the typical flavors. We found that the content of alcohols and aldehydes has a high abundance in Japanese soy sauce, but small portion of pyrazines and esters. Based on electronic nose and GC-MS analysis, Koikuchi Shoyu gives more contribution to aroma compounds, while Usukuchi Shoyu and Amakuchi Shoyu give the sourness and sweetness features based on electronic tongue and silylation GC–MS analysis. In this study, 50 kinds of sugars were detected that contributed to the sweetness of soy sauce. This study will provide new insight into the flavor characteristics of Japanese soy sauce that potentially contribute to the innovation and development of soy sauce.